Curious things : how can design research assist the development of audio-tactile tools for group music therapy sessions involving participants with dementia? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Fine Art with a Design endorsement at Massey University, Wellington, New Zealand - Byrne, Brittany (Massey University, 2014)
This design research project explores the creation of sensory tools for Music therapists involved with the care of patients with Dementia. The research aims to develop appropriate prototypes that provide a more engaging, stimulative and therapeutic experience for participants in group therapy music sessions. The purpose of this research is to assist facilitators and music therapists in providing residents with tools that allow for more explorative modes of active live music making. This mode of interaction is intended to spur a haptic and sonic curiosity amongst participants, that allow for more positive group experiences. The design research explores whether such tools are able to effectively assist Music therapy sessions for dementia patients through evaluating responses to ergonomic, haptic, sonic and visual properties in the object. The study involved a qualitative design research methodology using co-creative, iterative design approaches. Methods and processes involved user observations, rapid prototyping, user diaries, ongoing prototype workshops, user testing and a focus group.
Keywords: Dementia patient therapy; Music therapy; Audio-tactile tools; Musical instrument design